Effect of temperature and time of pasteurization on the milk quality during storage - Abubakar .; Triyantini .; R Sunarlim; H Setiyanto; Nurjannah . (Indonesian Center for Animal Research and Development (ICARD), 2001)
A study on the effect of temperature and time of pasteurization on the milk quality during storage was carried out using fresh milk. The aim of the experiment was to asses the storage time of pasteurized milk for consumption without nutrient losses. A completely randomized factorial design, 2 x 8 was used, with pasteurization temperature (T), consisted of 2 levels, the low temperature long time (LTLT), i.e. fresh milk was warmed at 65oC for 30 minutes (T1) and the high temperature short time (HTST), i.e. fresh milk was warmed at 71oC for 15 seconds (T2); and storage time (S), consisted of 8 levels, i.e. 0, 3, 6, 9, 12, 15, 18, and 21 hours respectively, as the factors, with 3 replicates. Parameters measured were alcohol test, water, fat, and protein concentrations, and microbial population of pasteurized milk during storage. Data were analyzed using analysis of variance and simple linear regression. The result showed that water and fat concentrations and microbial population was not significantly different (P>0.05) in pasteurization temperature treatment, but was significantly different (P<0.05) due to storage time treatment. Meanwhile, the protein concentration was significantly different (P<0.05) either in pasteurization temperature or storage time. It was concluded that pasteurized milk was still suitable for consumption at 15-21 hours storage, while protein concentration tended to be better when was pasteurized at 65oC. Key words: Pasteurized milk, storage quality